Relationship between Age and Gender with Acceptance of Covid-19 Vaccination in the West Kawangkoan Health Center Work Area (HEALTH CARE: JURNAL KESEHATAN, 2022)
Introduction: The one way to prevent the spread of COVID-19 is vaccination. The provision of the Covid-19 vaccine in Indonesia has now reached 3 stages, namely primary vaccinations 1 and 2 and added a 3rd or booster vaccination. However, in some areas the coverage of stage 2 vaccination is still